2014
DOI: 10.1103/physreve.89.062912
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization in a mechanical resonator array coupled quadratically to a common electromagnetic field mode

Abstract: Optomechanical systems are based on the nonlinear coupling between the electromagnetic (EM) field in a resonator and one or more bulk mechanical resonators such that the frequency of the EM field resonator depends on the displacement coordinates of each of the mechanical resonators. In this paper we consider the case of multiple mechanical resonators interacting with a common field for which the frequency of the EM resonance is tuned to depend quadratically (to lowest order) on the displacement of the resonato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Everywhere to the left of the bold red dashed line (which once more marks the saddle-node bifurcations of limit cycles) there exists one stable limit cycle and one unstable limit cycle. This figure was published in [4]. of R i0 H ir0 = 1.…”
Section: Declaration By Authormentioning
confidence: 99%
See 4 more Smart Citations
“…Everywhere to the left of the bold red dashed line (which once more marks the saddle-node bifurcations of limit cycles) there exists one stable limit cycle and one unstable limit cycle. This figure was published in [4]. of R i0 H ir0 = 1.…”
Section: Declaration By Authormentioning
confidence: 99%
“…Perhaps the most elegant explanation for this phenomenon was described by Kuramoto [38], who showed that for every weakly coupled nearly identical phase-only limit cycle oscillator, the long-term dynamics are given by [33] Using the order parameter, Kuramoto attempted to explain why the sudden onset of synchronization occurred above a certain value of K. In terms of the order parameter, his model is reduced to 4) making the dependence of the individual oscillators onr andψ explicit, so rather than each oscillator depending on itself and each of the N − 1 others, each oscillator depends on itself andr andψ. Using this form, Kuramoto noticed that the effective strength of the coupling is Kr, so a steady state value ofr = 0 just gave independent motion of the oscillators at their natural frequencies, whilstr ≈ 1 gave the near-maximum value for the effective strength, attracting more oscillators to the synchronized pack, thereby further strengthening the effective coupling and so on.…”
Section: The Kuramoto Modelmentioning
confidence: 99%
See 3 more Smart Citations